Exposição à mídia e personalidade: efeitos distais no cyberbullying - Leal, Ludwig Félix Machado (2022)
The general objective of this dissertation is to analyze the relationship between exposure to violent and prosocial media and personality with the cyberbullying through the General Model of Aggression - GAM. Four studies were planned, the first is a systematic review of the literature. In the first study, positive cyberbullying results were found in all sample examples. The second and third consist of psychometric studies, which are, respectively, exploratory (N = 263; M age = 29.1) and confirmatory (N = 266; M age = 30.2) of the Extended version of the content-based media exposure scale (C-ME2). Finally, the last one has a correlational design (N = 265; M age = 27.2) considering the relationships between the variables already highlighted. Validation studies showed that the scale presented a satisfactory internal consistency index for both factors, estimating a factor model indicating structural adequacy of this construct for samples of brazilian people. The results of the last study demonstrate that exposure to antisocial content on different media platforms is positively correlated with cyber aggression and cyber victimization, being the antisocial media exposure a significant mediator of this relationship. In addition, a mediation model was tested indicating that emotional stability does not directly impact cyber victimization, it only happens when considering the scenario in which the individual is a cyber aggressor.